2007
DOI: 10.1111/j.1460-9568.2007.05540.x
|View full text |Cite
|
Sign up to set email alerts
|

Kynurenic acid blocks nicotinic synaptic transmission to hippocampal interneurons in young rats

Abstract: The tryptophan metabolite kynurenic acid can block glutamate at ionotropic receptors, but recent evidence suggests a more potent antagonistic action at alpha7 nicotinic receptors for acetylcholine on cultured neurons. The present study examines activity of kynurenic acid at those nicotinic receptors, which mediate cholinergic neurotransmission onto interneurons in the rat hippocampus. Intracellular recordings were made from pyramidal cells and interneurons in the presence of atropine, bicuculline methobromide,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
74
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(76 citation statements)
references
References 48 publications
1
74
0
1
Order By: Relevance
“…KYNA is also an antagonist of the ␣7-nicotinic acetylcholine receptor (1,27,43,53). KYNA was recently identified as an endogenous ligand for an orphan G-protein-coupled receptor (GPR35) that is predominantly expressed in immune cells (57).…”
mentioning
confidence: 99%
“…KYNA is also an antagonist of the ␣7-nicotinic acetylcholine receptor (1,27,43,53). KYNA was recently identified as an endogenous ligand for an orphan G-protein-coupled receptor (GPR35) that is predominantly expressed in immune cells (57).…”
mentioning
confidence: 99%
“…38 Furthermore, as discussed by Heyes and colleagues, 39 the concentration of quinolinic acid in the human brain and CSF is 1-3 orders of magnitude above control levels in inflammatory disorders that are associated with neurologic deficits, suggesting that a putative decline from normal quinolinic acid levels after ATD is unlikely to have any important functional significance. Kynurenic acid also has an antagonistic action at nicotinic receptors, 40 and reducing rat brain kynurenic acid with an inhibitor of kynurenine aminotransferase, the enzyme that converts kynurenine to kynurenic acid, improves performance in the Morris water maze, suggesting that kynurenic acid is normally present in physiologically relevant concentrations in the brain. However, ATD does not lower human plasma kynurenic acid levels.…”
Section: Decrease In Metabolites Along the Kynurenine Pathwaymentioning
confidence: 99%
“…However, studies from numerous laboratories have demonstrated that KYNA also inhibits ␣7 nicotinic acetylcholine receptors (nAChRs) (Hilmas et al, 2001;Alkondon et al, 2004;Lopes et al, 2007;Stone, 2007;Arnaiz-Cot et al, 2008). Identifying the molecular targets that are accessible to the actions of endogenously produced KYNA in the brain is key to understanding the pathophysiology of a number of catastrophic neurological disorders in which brain levels of KYNA are altered, including Alzheimer's disease, schizophrenia, and Huntington's disease (Beal et al, 1992;Baran et al, 1999;Erhardt et al, 2007).…”
Section: Introductionmentioning
confidence: 99%